Rendering of the Advanced Technology Laboratories building - Cal Poly Public Affairs:::::::::; Doug Allen::::::::: (1999)
The Advanced Technology Laboratories building, dedicated in 1999, was funded by industry, the National Science Foundation, providing a new home for faculty and student research in engineering and computer science.